HIGHER ORDER THINKING SKILL (HOTS) MATHEMATICS INSTRUMENT TEST BASED ON MACROMEDIA FLASH FOR JUNIOR SECONDARY SCHOOL STUDENTS IN BENGKULU CITY - Edi Susanto; Agus Susanta; Rusdi Rusdi (DHARMA RAFLESIA, 2020)
One of the demands of the output of students learning in junior secondary shool, especially in mathematics was the ability to think at a higher level. Some students still had difficulty in solving mathematical  problems based  HOTS because of students not familiar with the problems. So it was  necessary to conduct training for mathematics teachers in preparing HOTS mathematical instruments and applying it in the form of computer-based tests using macromedia flash. The participants of the  training  were 30  secondary mathematics teachers the members of subject teachers  forum (MGMP)  that  consisted  of teachers of public and private junior scondary schools in Bengkulu City. The results of the training activities obtained 40 multiple choice questions from the results of the development of HOTS mathematical instruments. The instrument consisted of each 20 questions for grade  VII and grade VIII. The participants' responses to the training showed that the increasing  knowledge of the particpants, where the average knowledge of the participants was 35, and the post-test results showed that the increasing  knowledge of the participants in  preparing  HOTS instruments with an average was 62.75. The results of the development of the instrument had met the criteria of valid, reliable, discrimination index,  and difficulty levels. The 40 items of HOTS  instruments that developed were applied in Macromedia flash software.